Analisis Dampak Pembangunan Pembangkit Listrik Tenaga Energi Baru Terbarukan di Seluruh Indonesia terhadap Ekonomi Indonesia - Fadhilah, Revani; Susanti, Hera (Jurnal Kebijakan Ekonomi, 2019)
This thesis discusses the impact of Renewable Energy Power Plant Development in Indonesia on Economy at Indonesia. This research is quantitative descriptive design using Data Input-Output Indonesia 2010 to measuring economic impact. The results showed that the development of Renewable Energy Power Plant Development in Indonesia have a positive impact on the Indonesia economy, because it can create an increase in output, gross value added, and public revenue. The economic impact of the creation of the output in construction phase amounting to Rp. 152.028,12 billion, increased public revenue amounting to Rp. Rp. 19.486,20 billion, and the creation of gross value added amounted to Rp. 59.374,34 billion. The economic impact of the creation of the output in operation phase amounting to Rp. 148.120,84 billion, increased public revenue amounting to Rp.10.423,41 billion, and the creation of gross value added amounted to Rp.47.052,87 billion. Keywords: Renewable Energy, Power Plant, Economic Impact, Input Output Table